Crude protein level in the diet and supplemented calcium in laying hens. - Santos-Ricalde , Ronald (2024)
The laying percentage and egg weight are affected by the crude protein (CP) level and calcium (Ca) harms eggshell weight and the broken eggs percentage. In this experiment, conducted at the poultry facilities of the Faculty of Veterinary Medicine and Animal Science at the Autonomous University of Yucatán, Mérida, México, the effect of two CP levels (16% and 18%) and four levels of calcium supplementation in 2 mm particles (0, 2, 4, and 6 g/hen/day) on egg production and quality was measured. One hundred and ninety-two of 68 weeks-old hens were used at the beginning of the experiment. The hens were housed in cages; three cages with two hens and six cages with three were randomly assigned to each treatment. Diets were elaborated with 4.0% Ca. Hens were fed daily ad libitum and supplemented every second day with Ca grit additional to the diet, as the corresponding treatment. The experiment lasted 8 weeks and production and traits variables were measured every two weeks. The experiment was a completely randomized design with a factorial arrangement and repeated measures where the plot was the cage (experimental unit); the Error A was experimental, being the cage within treatments (protein and calcium combinations), and the Error B was residual. A higher egg and albumen weight  (p < 0.05) were found in the diet with 16% PC (63.9 y 39.0 g, respectively), compared to 18%  (62.5 g and 38.0 g, respectively). Shell weight was lower (p < 0.05) in hens with 6 g of Ca compared to the other levels (shell weights 5.8, 5.8, 5.9, and 5.4 g for treatments 0, 2, 4, and 6 g of supplemented Ca, respectively). In summary, neither an increase in the CP content of the feed nor calcium supplementation was beneficial in laying hens over 68 weeks of age.